Animated Video Media for Flood Disaster Mitigation for Fifth Grade Elementary School Students - Aditiya Aditiya; Hamdan Tr Atmaja; Deby Luriawati (Journal of Primary Education, 2022)
Media are very necessary in the learning process. This research focused on the development of video learning media for flood disaster relief as preliminary knowledge for fifth-grade students. The purposes of this study are to use need analysis, questionnaires from media and material experts, and pre-test and post-test questions. The collected sample were from a total of 16 students, fifth-grade, SD Labschool Unnes, Gajahmungkur district. The research methods applied were Research and Development with data collection using interview guides, teacher-student needs questionnaires, teacher-student effectiveness questionnaires, and validation questionnaires from media and material experts to guide the development of research and development by determining necessity and relevance, and pre-test and post-test. The tests aim to determine the effectiveness of animated video media in mitigating flood disasters. The data survey concluded that the existence and development of learning media was necessary and suitable to use based on validation evaluations by media experts. On the other hand, material experts achieved a percentage of 87%, which is included in the very practical category. Based on the t-test results, it can be said that the computed t is larger than the table t (7.121 > 1.753). It was rejected and it was accepted. The results of the t test showed that there was a significant influence of using animated video media for flood disaster mitigation on student learning outcomes. The results of the N-Gain Test show the difference between the average value of Pre-test and Post-test is 23,438 and the N-Gain Value is 0,5119, which means it is included in the medium criteria. So, it can be concluded that there is an improvement in Pre-test and Post-test learning outcomes with moderate criteria. The benefits of this research are to improve students’ knowledge about the material, to describe and explain about the media, to examine the media validity, and to understand the media effectiveness.